Psychosocial interventions for improving marital intimacy, sexual satisfaction, and quality of life of women and couples with infertility problems in low and middle-income countries: Systematic review protocol - Stella Sarpomaa Oppong; Florence Naab; Isaiah Osei Duah; Samuel Ankamah; David Owiredu; Francisca Happy Ametor; Mercy Monde Imakando; Josephine Mpomaa Kyei; Anthony Danso-Appiah (PLoS ONE, 2025)
Introduction Psychosocial interventions can be effective in improving health outcomes and quality of life of persons with infertility problems. This systematic review aims to document available psychosocial interventions for infertility-related problems in Low- and Middle-Income Countries (LMICs) and to assess their effectiveness for marital intimacy, sexual satisfaction, and quality of life (QoL) in people with infertility problems. Methods Studies will be considered eligible if they are randomized controlled trials (RCTs), quasi-experimental studies, and Observational studies (cohort, case-control, cross-sectional studies) involving women and couples with infertility problems and living in a LMIC who received a psychosocial intervention to improve marital intimacy, sexual satisfaction, and QoL. We will search PubMed, SCOPUS, CINAHL, LILACS, CENTRAL, and PsycINFO (EBSCO) from inception to 31 st March 2025, without language restriction, using all the relevant search terms and their synonyms, singular and plural forms and British and American spellings, together with the individual countries according to the Sheffield Centre for Health and Related Research (ScHARR) 2022 classification of LMICs. We will also search conference proceedings, preprint repositories, dissertation databases, the World Health Organisation, and government databases for additional studies. We will contact trial registries and experts for unpublished trials and hand-search reference lists of retrieved papers for studies missed by our searches. The retrieved studies will be exported to Rayyan for de-duplication and study selection using a pre-tested study selection flowchart developed from the study eligibility criteria. At least two reviewers will independently select studies, extract data with pretested data extraction sheet, and assess the quality of the included studies using validated tools. Dichotomous data will be assessed and reported as odds ratio (OR) or risk ratio (RR), and for continuous outcomes, mean difference (MD) will be used; all will be reported with their 95% confidence interval (CI). Heterogeneity will be assessed graphically by inspecting overlapping CIs and quantitatively using the I 2 statistic. Sensitivity analysis will be performed to test the robustness of the pooled estimates if the data permit, and the overall quality of the evidence will be assessed using the GRADE approach. Expected outcomes This systematic review and meta-analysis will identify effective psychological interventions and elaborate on the specific components to optimize and improve the psychosocial well-being of persons with infertility experiencing problems with sexual satisfaction and intimate relationships. The review will also uncover previously misclassified effective interventions due to limited data and small sample sizes from underpowered primary studies. Highlighting the existing evidence on available psychosocial interventions will inform clinical application, public education, and counselling services to optimize QoL of infertile couples and, importantly, inform the design of further studies to interrogate the region-specific application of these interventions. Dissemination and protocol registration The findings of this study will be disseminated through stakeholder forums, conferences, and peer-reviewed publications. The review protocol has been registered in the International Prospective Register for Systematic Reviews (PROSPERO)- CRD CRD42023480729.